Conscription and Crime - Galiani, Sebastian (World Bank, Washington, DC, 2012)
The initiation in criminal activities is, typically, a young phenomenon. The study of the determinants of entry into criminal activities should pay attention to major events affecting youth. In many countries, one of these important events is mandatory participation in military service. The objective of this study is to estimate the causal relationship between mandatory participation in military service and crime. The authors exploit the random assignment through a draft lottery of young men to conscription in Argentina to identify this causal effect. Their results suggest that participation in military service increased the likelihood of developing a criminal record in adulthood (in particular, for property and weapon-related crimes).